Sport medicine research needs funding: the International football federations are leading the way - Ekstrand, J.; Dvorak, J.; D'Hooghe, M. (British Journal of Sports Medicine, 2013)
In a recent BJSM editorial, Dr John Orchard highlighted that good injury surveillance requires funding. Funding is a key factor for injury studies and the process of building up and maintaining a database and a register. Guaranteed funding for a period of time favours retention of good quality staff and permits quality control.